PEMBUATAN MEUSEUKAT MENGGUNAKAN TEPUNG KOMPOSIT DARI SUKU (Artocarpus altilis) DAN TERIGU SERTA PENAMBAHAN NENAS (Ananas comosus L.) - Yanti Meldasari Lubis; Syarifah Rohaya; Huri Afrina Dewi (Jurnal Teknologi dan Industri Pertanian Indonesia, 2012)
This study aimed to determine the effect of composite flour ratio and the pineapples percentage that is added to the meuseukat produced. Based on the results, meseukat has a value of 34.30% moisture content, ash content of 0.52%, 22.98% of sucrose levels, fat of  82%, crude fiber content of 2.22%, hardness 0.0043 kg / cm2, organoleptic values of color 3.19 (neutral), aroma from 3.07 to 3.43 (neutral), taste of 3.16 to 3.63 (neutral), the texture of 3.23 (neutral). The best treatment of meusekat was proportion of  breadfruit flour and wheat flour (30: 70) and the addition of pineapple 60% . The addition of breadfruit flour causes aroma of  meuseukat less preferred by the panelists as the aroma of breadfruit more specific but the taste of meusekat with the addition of breadfruit flour is preferred